2019
DOI: 10.1136/bmj.l1375
|View full text |Cite
|
Sign up to set email alerts
|

The remarkable impact of bivalent HPV vaccine in Scotland

Abstract: New analyses show substantial cross protection and herd immunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The same 2 members of the research team compared their classifications and scoring, and if consensus could not be reached, a third member of the research team (LKAS) made the final decision. In addition, we extracted information about the characteristics of the paper (study design, research question, or objective), journal (journal name and year published), and author (names, affiliations, and conflicts of interest; refer to Multimedia Appendices 1 and 2 [52,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] for results of the top 20 most shared papers obtained from the vaccine-confident and vaccine-hesitant communities). These data were used to conduct bibliometric analyses of the journal and descriptive analysis of the research content shared by each community, which are further described in the following sections.…”
Section: Typology Of Evidence For Thematic and Critical Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…The same 2 members of the research team compared their classifications and scoring, and if consensus could not be reached, a third member of the research team (LKAS) made the final decision. In addition, we extracted information about the characteristics of the paper (study design, research question, or objective), journal (journal name and year published), and author (names, affiliations, and conflicts of interest; refer to Multimedia Appendices 1 and 2 [52,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] for results of the top 20 most shared papers obtained from the vaccine-confident and vaccine-hesitant communities). These data were used to conduct bibliometric analyses of the journal and descriptive analysis of the research content shared by each community, which are further described in the following sections.…”
Section: Typology Of Evidence For Thematic and Critical Appraisalmentioning
confidence: 99%
“…For example, in the orange cluster, 1 particularly influential physician circulated an editorial paper about the effectiveness of the HPV vaccine, which indicated that high HPV vaccine coverage could eradicate cervical cancer within a few decades [74]. A science correspondent for a pre-eminent American newspaper was the leading influencer in the light green cluster wherein the primary paper circulated was an editorial, also focused on effectiveness, related to the positive impacts of HPV vaccination in Scotland [75]. Finally, in the blue cluster, a leading cancer prevention researcher from a British research institute was the leading influencer and author of the scientific papers circulated.…”
Section: Vaccine-confident Social Networkmentioning
confidence: 99%
“…But, four patients who had apparent anaphylactic reactions to it were negative skin test to vaccine, baker's yeast, and polysorbate 80. Vaccination in adolescents was associated with a high rate of syncope that accounted for some events diagnosed as anaphylaxis (Brotherton, 2019) Influenza: Some vaccines contain egg protein, but allergic reactions were due to some other components as well. In Japan in 2011 & 2012, there was a three-to fivefold increase in influenza vaccine-associated anaphylaxis reported in 36 children without egg allergy, of whom 19 were subsequently investigated (Nagao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a more complete picture of HPV infection age-patterns may provide parameters to better understand the global nature of HPV infection and the impact of HPV vaccination in future screening cohorts. [7][8][9] Additionally, it is relevant to evaluate the differences of age at the triage step in settings where a second test is used to detect precancerous lesions among HPV-positive women. When using HPV as the primary screening test, a certain proportion of women may not develop disease as they may clear the infection.…”
Section: Introductionmentioning
confidence: 99%